Adverse Birth Outcomes Associated with Maternal Smoking and Polymorphisms in the N-Nitrosamine-Metabolizing Enzyme Genes NQO1 and CYP2E1 - Sasaki, Seiko; Sata, Fumihiro; Katoh, Shizue; Saijo, Yasuaki; Nakajima, Sonomi; Washino, Noriaki; Konishi, Kanae; Ban, Susumu; Ishizuka, Mayumi; Kishi, Reiko (American journal of epidemiology, 2008)
Maternal smoking during pregnancy can result in both pregnancy complications and reduced size of the fetus and neonate. Among women who smoke, genetic susceptibility to tobacco smoke also is a likely causative factor in adverse pregnancy outcomes. A prospective cohort study was conducted among 460 pregnant women who delivered live singletons in Sapporo, Japan, from 2002 to 2005. Multiple linear regression models were used to estimate associations of maternal smoking and polymorphisms in two genes encoding N-nitrosamine-metabolizing enzymes—NAD(P)H: quinone oxidoreductase 1 (NQO1) and cytochrome P-450 2E1 (CYP2E1)—with birth size. Among infants born to smokers with the NQO1 homozygous wild-type allele, birth weight, birth length, and birth head circumference were significantly reduced (p < 0.01 for each factor). For the homozygous wild-type CYP2E1 allele, birth weight was lower by an estimated 195 g (standard error, 55; p < 0.001) among smokers. These genotypes did not confer adverse effects among women who had never smoked or who quit smoking during the first trimester. The adverse effects of maternal smoking on infant birth size may be modified by maternal genetic polymorphisms in N-nitrosamine-metabolizing enzymes among Japanese subjects. These results may help in directing smoking cessation interventions during pregnancy, especially among susceptible women.